Pengaruh Ekstrak Kulit Batang Tumbuhan Kelor(Moringa oleifera)Terhadap AngkaKonsepsi Mencit (Musmusculus) ICR Jantan - St Aisyah S; Adnan Gassing (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2016)
This research aims to determine the effect of Moringa rod extract toward the conception rate of male ICR mice (Mus musculus). This study is an experimental study using completely randomizeddesign (CRD), which consists of one control (A0) and four treatments (A1, A2, A3 and A4) with adose of 75 mg/kg. Treatment is given for 1 week, 2 weeks, reversibility for one week and twoweeks.Provision of intra peritonial with a volume of 0.5 cc/mice. The parameters observed as anindicator is the number of corpus luteum, implantation percentage, percentage of live fetuses andthe percentage of intra uterine death in female mice as testmating pairs in conception rates of malemice. The results showed that the extract of Moringa rod with 75 mg/kg dose given to male micesignificantly affect the percentage of implantation and the percentage of live fetuses in female mice.But did not significantly affect the amount of the corpus luteum and the percentage of intra-uterinedeath. From the results, this study concluded that the extract of Moringa rodeffect on conceptionrates male ICR mice. The 75 mg/kgdose has not shown resilience fertility in male mice eventhough their use is stopped for up to three weeks. In other words, the moringa rod extract mayinterfere with the reproductive function of male ICR mice (Mus musculus), potentially as an activeingredientofanti-fertility